How to accelerate the end of hunger and undernutrition - von Grebmer, Klaus (Karger AG, 2018)
In recent decades, global undernourishment rates have declined, and health and nutrition have improved. Yet the pace of progress has been shamefully slow. To break the cycle of poverty, hunger, and undernutrition, the problems of hunger and undernutrition must be addressed first. The socioeconomic costs and detrimental effects on human health of hunger and undernutrition perpetuate poverty; if they persist, there will be no end to poverty.